Growth and physiological adaptation of whole plants and cultured cells from a halophyte turf grass under salt stress - Tada, Yuichi (Oxford University Press, 2014)
Understanding the mechanisms used by halophytic members of the Poaceae to cope with salt stress will contribute to the knowledge necessary to genetically engineer salt-tolerant crops. In this study, we identified a genotype of Sporobolus virginicus, a halophytic turf grass collected in Japan, and investigated its growth rate, ion concentration and secretion, and proline concentration in comparison with the reported properties of genotypes collected from the USA, South Africa and Egypt. Surprisingly, the Japanese genotype showed a salinity tolerance up to 1.5 M NaCl, a 3-fold higher concentration than seawater salinity. Shoot growth was stimulated by 100 mM NaCl and root growth was stimulated at salinities of up to 1 M NaCl. Accumulation of Na(+) and CI(−) in shoots and roots was rapidly elevated by salinity stress but did not exceed the levels required for osmotic adjustment, due in part to ion secretion by salt glands, which are present in genotypes of S. virginicus. However, the Japanese genotypes accumulated K(+) to a higher level than other genotypes, resulting in a relatively high K(+)/Na(+) ratio even under salinity stress. An increase in proline concentration was observed that was proportional to the NaCl concentration in the culture solution and might partially account for osmotic adjustment in the shoots. We also generated and characterized cultured cells of S. virginicus. In 500 mM NaCl, the cultured cells showed an enhanced growth compared with cultured cells of rice. The concentration of Na(+) and CI(−) in the cultured cells in 300–500 mM NaCl was lower than in 100 mM NaCl. Cultured cells of S. virginicus accumulated proline to higher levels than rice cells cultured under salinity stress. The active regulation of Na(+), Cl(−) and K(+) influx/efflux and proline accumulation might be involved in salt tolerance mechanisms at the cellular level as well as in planta.